Histological quantification of astrocytosis after cerebral infarction: a systematic review. (1st July 2013) - Ostergaard, Peter J.; Jensen, Matthew B.
<x xml:space="preserve">Abstract</x> Accurate histological quantification of astrocytosis after cerebral infarction is needed as this process may affect, and be affected by, many potential restorative treatments under investigation. We performed a systematic review to determine the most reliable histological method reported for measurement of postinfarction astrocytosis. We found reports of multiple techniques to quantify various parameters of immunohistochemical staining for the astrocyte marker glial fibrillary acidic protein on photomicrographs with several software packages. We found no studies directly comparing techniques. We conclude that the reported methods seem reasonable, but the descriptions were often insufficiently detailed to allow for replication, and the lack of comparison data makes the best method unclear. Further research is needed to optimize the analysis of this important tissue outcome after cerebral infarction.